2022
DOI: 10.3389/fendo.2022.964132
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity, sedentary behavior, and the risk of type 2 diabetes: A two-sample Mendelian Randomization analysis in the European population

Abstract: Physical activity (PA) and sedentary behaviors (SB) have been linked to the risk of type 2 diabetes (T2DM) in observational studies; however, it is unclear whether these associations are causative or confounded. This study intends to use summary genetic data from the UK Biobank and other consortiums in conjunction with the two-sample Mendelian Randomization (MR) approach to solve this problem. The inverse variance weighted (IVW) technique was utilized as the primary analysis, with sensitivity analyses using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 55 publications
1
7
0
Order By: Relevance
“…Adults spent a mean of 8.2 hours per day (range 4.9–11.9 h/day) in SB during waking hours (i.e., excluding the sleep period) [ 2 , 3 ]. Extended periods of time spent in SB activities have been associated with the development of cardiovascular diseases, diabetes type 2, and a high risk of mortality [ 4 , 5 ]. The mortality rate is increased by 2% for each hour sitting and increased further (almost 8%) if the sitting time is more than 8 h a day [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Adults spent a mean of 8.2 hours per day (range 4.9–11.9 h/day) in SB during waking hours (i.e., excluding the sleep period) [ 2 , 3 ]. Extended periods of time spent in SB activities have been associated with the development of cardiovascular diseases, diabetes type 2, and a high risk of mortality [ 4 , 5 ]. The mortality rate is increased by 2% for each hour sitting and increased further (almost 8%) if the sitting time is more than 8 h a day [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the general adult population, self-reported MVPA took longer than APA [ 53 ]. PA data obtained from self-reported MVPA and APA differed conceptually, and these differences increased with activity and intensity levels [ 54 ]. This discrepancy regarding causality with myopia may be justified by these possibilities.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, LST people often have abnormal eating habits, they usually don’t have a habit of breakfast and the intake of vitamin and dietary fiber in the diet is low, fat composition is relatively high [ 32 ].These irregular eating habits can induce the formation of gallstones [ 33 ] and gallstones is the most common trigger of AP in advanced countries [ 34 ]. Secondly, A recent Mendelian randomization study has demonstrated that LST increases the risk of type 2 diabetes causally [ 35 ]. Dipeptidylpeptidase-4 (DPP4) inhibitors and Glucagon-like peptide-1 receptor agonist (GLP-1RAs) are important treatments for T2D.These medicines may increase the risk of pancreatitis [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%